Preparation and characterization of dye sensitized solar cell based on nanostructured Fe2O3 - Cavas, M.; Gupta, R. K.; Al-Ghamdi, Ahmed A.; Gafer, Zarah H.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Elsevier, 2013)
Thin films of hematite (Fe2O3) were synthesized using sol gel spin coating method on fluorine doped tin oxide and glass substrates. The synthesized Fe2O3 film was used to fabricate ruthenium dye sensitized solar cells. The average transmittance of the Fe2O3 film was observed to be more than 75% in wavelength range of 600-900 nm. The optical band gap of Fe2O3 films was calculated using transmittance data and observed to be 2.21 eV. The current voltage characteristics of the solar cell showed that the photocurrent of the solar cell is increased with increase in the light illumination intensity. The output power voltage characteristics indicate that the output power of the solar cell improved is increased with irradiance. Although the efficiency of the Fe2O3 film based solar cell is poor for practical applications, Fe2O3 film can be used in dye sensitized solar cells. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Fe2O3; Ruthenium dye; Dye sensitized solar cells